Change in soil fungal community structure driven by a decline in ectomycorrhizal fungi following a mountain pine beetle (Dendroctonus ponderosae) outbreak. Issue 2 (23rd September 2016) - Pec, Gregory J.; Karst, Justine; Taylor, D. Lee; Cigan, Paul W.; Erbilgin, Nadir; Cooke, Janice E. K.; Simard, Suzanne W.; Cahill, James F.
Summary: Western North American landscapes are rapidly being transformed by forest die‐off caused by mountain pine beetle ( Dendroctonus ponderosae ), with implications for plant and soil communities. The mechanisms that drive changes in soil community structure, particularly for the highly prevalent ectomycorrhizal fungi in pine forests, are complex and intertwined. Critical to enhancing understanding will be disentangling the relative importance of host tree mortality from changes in soil chemistry following tree death. Here, we used a recent bark beetle outbreak in lodgepole pine ( Pinus contorta ) forests of western Canada to test whether the effects of tree mortality altered the richness and composition of belowground fungal communities, including ectomycorrhizal and saprotrophic fungi. We also determined the effects of environmental factors (i.e. soil nutrients, moisture, and phenolics) and geographical distance, both of which can influence the richness and composition of soil fungi. The richness of both groups of soil fungi declined and the overall composition was altered by beetle‐induced tree mortality. Soil nutrients, soil phenolics and geographical distance influenced the community structure of soil fungi; however, the relative importance of these factors differed between ectomycorrhizal and saprotrophic fungi. The independent effects of tree mortality, soil phenolics and geographical distance influenced the community composition of ectomycorrhizal fungi, while the community composition of saprotrophic fungi was weakly but significantly correlated with the geographical distance of plots. Taken together, our results indicate that both deterministic and stochastic processes structure soil fungal communities following landscape‐scale insect outbreaks and reflect the independent roles tree mortality, soil chemistry and geographical distance play in regulating the community composition of soil fungi.